The Effect of Health Education about Back Massage on the Level of Knowledge in Adapting Labor Pain - Neneng Safitri; Karmita Sari; Rena Oki Alestari; Ivana Devitasari (KHD Production, 2025)
Labor pain is a physiological phenomenon experienced by every pregnant woman. However, the response to this pain varies greatly, from screaming and crying to getting angry. One non-pharmacological method that can be used to reduce labor pain is back massage. This technique involves applying pressure to soft tissue, such as muscles, tendons, or ligaments, without causing joint movement. Massage not only relieves pain but also increases relaxation and improves blood circulation. However, an initial Bukit Hindu Palangka Raya Community Health Center survey showed that most pregnant women did not understand this technique. Therefore, this study aims to evaluate the effect of health education regarding back massage techniques on the level of knowledge of pregnant women in adapting to labor pain. This research uses a pre-experimental design with a